Aluminum sol combined with silicon carbide spray coating, protective layer and preparation method and application thereof
By using aluminum sol in spray coatings to combine silicon carbide and generating Ti3SiC2 bonding phase through in-situ reaction, the problem of poor performance of existing spray coatings in high temperature environments is solved, and the high strength, wear resistance and Thermal shock stability and energy-saving and environmentally friendly.
Patent Information
- Application Number
- CN202411667705.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing spray coatings have poor performance in high temperature environments, high rebound rate, poor density, large dust, low service life, and low demolding strength in low temperature environments, making them easy to freeze.
Aluminum sol combined with silicon carbide as the main component of the spray coating is used to generate the Ti3SiC2 bonding phase through in-situ reaction of titanium dioxide, C and metal Si in ballast asphalt, thereby improving the high-temperature performance and thermal shock stability of the sprayed protective layer.
It has achieved the advantages of high strength, good wear resistance, strong thermal shock stability, energy-saving and environmental protection of sprayed protective layer, and its service life is more than 3 years.
Smart Images

Figure CN119161754B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of refractory materials, and in particular to an aluminum sol combined with silicon carbide spray coating, a protective layer, and a preparation method and application thereof. Background Art
[0002] The hot blast furnace fork, blast furnace slag ditch, coke oven leg, cement kiln tertiary air damper, etc., with working temperature of 400℃~1400℃, are subject to high wind speed (wind speed above 20m / s), and are accompanied by a large amount of clinker and acid and alkali dust, chemical erosion, thermal stress caused by sudden temperature change, etc., which cause damage to the material structure. For this reason, the method of spraying high temperature resistant and wear-resistant spray coating on the construction surface of blast furnace lining, industrial kiln, etc. is adopted to repair and improve the wear resistance, erosion resistance and service life of the material structure.
[0003] At present, the spraying methods mainly include semi-dry spraying technology and wet spraying technology. For semi-dry spraying technology, during construction, the material is sent to the vicinity of the gun muzzle by high-pressure air, and the water and material delivered to the gun muzzle are quickly mixed and sprayed onto the construction surface of the blast furnace lining, industrial kiln, etc. that need to be repaired. However, this spraying method has problems such as high rebound rate, poor density, large dust, and low service life. For wet spraying technology, the spraying material except the coagulant is sent to the nozzle, mixed with the coagulant at the nozzle, and then sprayed onto the construction surface of the blast furnace lining, industrial kiln, etc.; this spraying method has the advantages of low rebound rate (generally less than 5%, much lower than the rebound rate of 15% to 30% of semi-dry spraying), high density, extremely low dust, and long service life.
[0004] At present, pure calcium aluminate cement and silica sol are generally used as binders in the spray coating materials used in wet spraying technology. Pure calcium aluminate cement will generate low-melting products in high-temperature environments, which makes its high-temperature performance poor. In addition, the baking and curing process of the spray protective layer after spraying is difficult to control, and the baking effect is not ideal, which in turn affects the quality and performance of the spray protective layer. In addition, silica sol has low demoulding strength at room temperature and is easy to freeze when used in low-temperature environments. Summary of the invention
[0005] To solve the above problems, the present application proposes an aluminum sol combined with silicon carbide spray coating, a protective layer and a preparation method and application thereof. The spray protective layer obtained by spraying the spray coating has the advantages of high strength, good wear resistance, strong thermal shock stability, energy saving and environmental protection.
[0006] This application is implemented through the following technical solutions:
[0007] One of the purposes of the present application is to provide a spray coating, comprising the following components: a base powder and an additive;
[0008] The matrix powder includes silicon carbide, alumina powder, spherical asphalt, titanium dioxide and silicon; the additive includes aluminum sol, dispersant and accelerator;
[0009] The mass fractions of the raw material components in the matrix powder include: 60% to 75% silicon carbide, 10% to 25% alumina powder, 2% to 7% spherical asphalt, 1% to 5% titanium dioxide and 2% to 4% silicon.
[0010] The spray coating provided by the present application uses silicon carbide with the characteristics of high hardness, high strength, high thermal conductivity, strong oxidation resistance and chemical corrosion resistance, which can improve the strength of the spray protective layer. Aluminum sol is used as a binder for silicon carbide materials to greatly improve the high-temperature performance of the material. The titanium dioxide, the C in the ball asphalt and the metal Si react in situ (reaction temperature 1350℃~1400℃) to generate a Ti3SiC2 binding phase. The reaction chemical formula is: 3TiO2+9C+2Si=Ti3SiC2+SiC+6CO. Ti3SiC2 has a high melting point (>3000℃) and good corrosion resistance. Its unique network structure and plastic properties at high temperatures can greatly reduce thermal stress and improve the thermal shock stability of the spray protective layer. The dispersant can promote the dispersion of the matrix powder in the aluminum sol. The coagulant accelerates the hardening rate of the spray coating.
[0011] In some possible implementations, taking the mass of the matrix powder as 100%, D represents the particle size of the silicon carbide, and the gradation distribution and mass fraction of the silicon carbide include: 5mm≤D<8mm is 10%~15%, 3mm≤D<5mm is 15%~25%, 1mm≤D<3mm is 15%~25%, 0.074mm≤D<1mm is 10%~20%, and D<0.074mm is 10%~20%. In this case, reasonable particle gradation makes the materials more tightly packed after mixing, which is conducive to improving the body density of the materials after spraying and making the protective layer more dense.
[0012] In some possible implementations, the purity of silicon carbide is above 97%, the purity of aluminum oxide is above 99.5%, the purity of titanium dioxide is above 98.5%, and the purity of silicon is above 99%. In this case, the use of high-purity silicon carbide, aluminum oxide, titanium dioxide and silicon can reduce the impurity content of the spray coating, so that the bonding system of the spray coating develops in the direction of low impurities or even no impurities. At the same time, the higher the purity of the material, the higher the activation energy of the material to react at high temperature, and the more complete the reaction.
[0013] In some possible implementations, the mass of the aluminum sol is 7% to 11% of the matrix powder.
[0014] In some possible implementations, the mass of the dispersant is 0.1% to 0.35% of the matrix powder. In some possible implementations, the mass of the coagulant is 0.7% to 1.6% of the matrix powder. In this case, the silicon carbide is the main component of the spray coating, and since silicon carbide itself has high hardness and high strength, the spray protection layer obtained by spraying can be made harder and stronger.
[0015] In some possible implementations, the D50 of the alumina powder is 1.0 μm to 2.0 μm. In this case, the particle size distribution of the activated alumina powder is uniform, which is easy to wrap the particles and make the spray coating structure more compact.
[0016] In some possible implementations, the carbon content in the spherical pitch is 55wt% to 60wt%. In this case, the spherical structure of the spherical pitch is easy to mix with other components; the high carbon content is easy to react with the Ti3SiC2 binding phase.
[0017] In some possible implementations, the particle size of the spherical pitch is less than 1 mm. In this case, the spherical pitch is filled between the large particles and the fine powder in the silicon carbide to make the material more dense.
[0018] In some possible implementations, the particle size of the titanium dioxide is less than 44 μm. In this case, the finer the particle size of the titanium dioxide, the stronger the activity, and the easier it is to react at high temperature.
[0019] In some possible implementations, the particle size of the silicon is less than 74 μm.
[0020] In some possible implementations, the mass fraction of Al2O3 in the aluminum sol is greater than 35%, the pH value is 3.5-4.5, and the average particle size is 10nm-100nm. In this case, the aluminum sol has a high solid phase content and a small particle size, and the bonding strength is higher.
[0021] In some possible implementations, the dispersant is a mixture of a polyethylene glycol polymer compound and sodium tripolyphosphate.
[0022] Furthermore, the mass of the polyethylene glycol polymer compound is 0.05% to 0.15% of the matrix powder, and the mass of the sodium tripolyphosphate (P3) is 0.05% to 0.25% of the matrix powder.
[0023] Furthermore, the molecular weight of the polyethylene glycol polymer compound is 12000 to 15000. In this case, the dispersant can fully disperse the silicon carbide powder and the binder (aluminum sol), significantly reducing the amount of water added during construction.
[0024] Furthermore, the polyethylene glycol polymer compound includes polyethylene glycol and / or polyethylene glycol dimethacrylate.
[0025] Furthermore, the polyethylene glycol polymer compound is a high-efficiency water reducer produced by BASF of Germany, model FS10.
[0026] In some possible implementations, the coagulant is a mixture of a saturated aluminum chloride solution and a saturated sodium chloride solution. In this case, the coagulant can cause the spray coating sprayed on the construction surface to quickly lose fluidity, so that the material does not fall off.
[0027] Furthermore, the mass ratio of the saturated aluminum chloride solution to the saturated sodium chloride solution is 2: 1. In this case, the rapid setting effect of the coagulant is optimal.
[0028] The second purpose of the present application is to provide a spray protective layer, wherein the raw material components in the spray protective layer include the spray coating material provided in the present application, and the thickness of the spray protective layer is 50mm~100mm.
[0029] The spray protective layer provided in this application has a flexural strength of 12MPa~20MPa at 110℃×24h; a compressive strength of 150MPa~200MPa; a flexural strength of 15MPa~25MPa at 1400℃×3h; and a compressive strength of 200MPa~250MPa. Excellent thermal shock stability (first heat to 1100℃ and keep warm for 30min, then cool in running water until the damage rate of the heated surface of the spray protective layer is about 50%, at which point the number of hot and cold cycles is 50~60 times). Wear resistance (110℃×24h) is 3cm 3 ~4.5cm 3 Therefore, the sprayed protective layer has the advantages of high strength, good wear resistance, strong thermal shock stability, energy saving and environmental protection. The service life of the sprayed protective layer provided in the present application is more than 3 years.
[0030] The third object of the present application is to provide a method for preparing the spray protective layer provided in the present application, comprising the following steps:
[0031] Obtaining the raw material components of the spray protective layer of the present application;
[0032] The matrix powder, aluminum sol and dispersant are mixed, and then mixed with a coagulant and sprayed on the surface of the target object to obtain a spray protective layer.
[0033] The preparation method of the spray protective layer of the present application comprises the following steps: mixing matrix powder, aluminum sol and dispersant to form a homogeneous mixture, and then adding a coagulant for spraying, thereby improving the bonding performance between the spray protective layer and the surface of the target object, and enhancing the strength and performance of the spray protective layer. The addition of a coagulant can also reduce construction time and improve construction efficiency. In addition, the preparation method adopts the spray coating provided by the present application, and the rebound rate during spraying is only 3% to 5%, which significantly saves the material cost of the spray coating, and can also reduce the number of spraying times and improve the overall efficiency of construction.
[0034] In some possible implementations, in the spraying step, the spraying pressure is 2MPa~4MPa, and the spraying speed is 10m 2 / s~20m 2 / s. In this case, the pressure and spraying rate are conducive to the flow of materials in the pipeline and the spraying of the spraying surface.
[0035] In some possible implementations, the target object includes a blast furnace lining construction surface or an industrial kiln construction surface.
[0036] A fourth purpose of the present application is to provide a spray coating for use in the field of industrial kilns. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present drawings or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present drawings. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.
[0038] Figure 1 This is an electron microscope image of the in-situ generated network Ti3SiC2 bonding phase in Example 1 of the present application.
[0039] The purpose, features and advantages of this figure will be further explained in conjunction with the embodiments with reference to the accompanying drawings. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is described and illustrated below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. Based on the embodiments provided in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0041] Obviously, the following descriptions are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios without creative work. In addition, it can also be understood that although the efforts made in this development process may be complicated and lengthy, for ordinary technicians in the field related to the content disclosed in this application, some changes in design, manufacturing or production based on the technical content disclosed in this application are just conventional technical means, and should not be understood as insufficient content disclosed in this application.
[0042] However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially the same structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.
[0043] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution, and all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0044] Example 1
[0045] Embodiment 1 proposes a spray coating, which is composed of the following raw material components:
[0046] Matrix powder: 73% silicon carbide, 15% alumina powder, 5% spherical asphalt, 3% titanium dioxide, 4% silicon;
[0047] Additives: 8% aluminum sol by weight of the matrix powder, 0.15% dispersant (a mixture of 0.05% FS10 and 0.1% sodium tripolyphosphate) by weight of the matrix powder, and 0.85% coagulant by weight of the matrix powder.
[0048] Wherein, taking the mass of matrix powder as 100%, D represents the particle size of silicon carbide, the graded distribution and mass fraction of silicon carbide are: 5mm≤D<8mm is 15%, 3mm≤D<5mm is 20%, 1mm≤D<3mm is 15%, 0.074mm≤D<1mm is 13%, and D<0.074mm is 10%;
[0049] The mass fraction of aluminum sol is 40%, the pH value is 4, and the average particle size is 35nm;
[0050] The coagulant is a mixture of a saturated aluminum chloride solution and a saturated sodium chloride solution in a mass ratio of 2:1.
[0051] Example 2
[0052] Embodiment 2 proposes a spray coating, which is composed of the following raw material components:
[0053] Matrix powder: 70% silicon carbide, 20% alumina powder, 4% spherical asphalt, 3% titanium dioxide, 3% silicon;
[0054] Additives: 9% of aluminum sol by weight of the matrix powder, 0.15% of dispersant (a mixture of 0.08% FS10 and 0.07% sodium tripolyphosphate) by weight of the matrix powder, and 0.85% of coagulant by weight of the matrix powder.
[0055] Wherein, taking the mass of matrix powder as 100%, D represents the particle size of silicon carbide, the graded distribution and mass fraction of silicon carbide are: 5mm≤D<8mm is 13%, 3mm≤D<5mm is 18%, 1mm≤D<3mm is 20%, 0.074mm≤D<1mm is 13%, and D<0.074mm is 6%;
[0056] The mass fraction of aluminum sol is 40%, the pH value is 4, and the average particle size is 35nm;
[0057] The coagulant is a mixture of a saturated aluminum chloride solution and a saturated sodium chloride solution in a mass ratio of 2:1.
[0058] Example 3
[0059] Embodiment 3 proposes a spray coating, which is composed of the following raw material components:
[0060] Matrix powder: 68% silicon carbide, 20% alumina powder, 5% spherical asphalt, 3.5% titanium dioxide, 3.5% silicon;
[0061] Additives: 9.5% of aluminum sol by weight of the matrix powder, 0.15% of dispersant (a mixture of 0.1% FS10 and 0.05% sodium tripolyphosphate) by weight of the matrix powder, and 0.7% of coagulant by weight of the matrix powder.
[0062] Wherein, taking the mass of matrix powder as 100%, D represents the particle size of silicon carbide, the graded distribution and mass fraction of silicon carbide include: 5mm≤D<8mm is 15%, 3mm≤D<5mm is 20%, 1mm≤D<3mm is 15%, 0.074mm≤D<1mm is 10%, and D<0.074mm is 8%;
[0063] The mass fraction of aluminum sol is 40%, the pH value is 4, and the average particle size is 35nm;
[0064] The coagulant is a mixture of a saturated aluminum chloride solution and a saturated sodium chloride solution in a mass ratio of 2:1.
[0065] Comparative Example 1
[0066] Comparative Example 1 proposes a spray coating, which uses pure calcium aluminate cement and silica sol as binders and is composed of the following components in parts by weight: 50 parts of brown corundum, 20 parts of silicon carbide, 5 parts of pure calcium aluminate cement, 25 parts of nano-calcium carbonate, 3 parts of silica sol, 2 parts of sodium hexametaphosphate, and 3 parts of Si3N4.
[0067] Comparative Example 2
[0068] Comparative Example 2 proposes a spray coating, which is composed of the following components by mass fraction:
[0069] Matrix powder: 76% silicon carbide, 15% alumina powder, 5% spherical asphalt, 4% silicon;
[0070] Additives: 8% aluminum sol by weight of the matrix powder, 0.15% dispersant (a mixture of 0.05% FS10 and 0.1% sodium tripolyphosphate) by weight of the matrix powder, and 0.85% coagulant by weight of the matrix powder;
[0071] Among them, the mass fraction of aluminum sol is 40%, the pH value is 4, and the average particle size is 35nm;
[0072] The coagulant is a mixture of a saturated aluminum chloride solution and a saturated sodium chloride solution in a mass ratio of 2:1.
[0073] Comparative Example 3
[0074] Comparative Example 3 proposes a spray coating, which is composed of the following components by mass fraction:
[0075] Matrix powder: 77% silicon carbide, 15% alumina powder, 5% spherical asphalt, 3% titanium dioxide;
[0076] Additives: 8% aluminum sol by weight of the matrix powder, 0.15% dispersant (a mixture of 0.05% FS10 and 0.1% sodium tripolyphosphate) by weight of the matrix powder, and 0.85% coagulant by weight of the matrix powder;
[0077] Among them, the mass fraction of aluminum sol is 40%, the pH value is 4, and the average particle size is 35nm;
[0078] The coagulant is a mixture of a saturated aluminum chloride solution and a saturated sodium chloride solution in a mass ratio of 2:1.
[0079] Comparative Example 4
[0080] Comparative Example 4 proposes a spray coating consisting of the following components by mass fraction:
[0081] Matrix powder: 78% silicon carbide, 15% alumina powder, 3% titanium dioxide, 4% silicon;
[0082] Additives: 8% aluminum sol by weight of the matrix powder, 0.15% dispersant (a mixture of 0.05% FS10 and 0.1% sodium tripolyphosphate) by weight of the matrix powder, and 0.85% coagulant by weight of the matrix powder;
[0083] Among them, the mass fraction of aluminum sol is 40%, the pH value is 4, and the average particle size is 35nm;
[0084] The coagulant is a mixture of a saturated aluminum chloride solution and a saturated sodium chloride solution in a mass ratio of 2:1.
[0085] In order to verify the progress of the spray coatings proposed in the examples of the present application, the spray coatings provided in the examples and comparative examples were sprayed using a wet spraying process to obtain a spray protective layer, and the thickness of the spray protective layer was 80 mm. The flexural strength, compressive strength, thermal shock stability, wear resistance and rebound rate of the spray protective layer were tested, and the results are shown in Table 1 below.
[0086] The spraying and testing steps of the wet spraying process are as follows:
[0087] 1) Wet spraying process steps: Mix the matrix powder (silicon carbide, aluminum oxide powder, spherical asphalt, titanium dioxide and silicon), aluminum sol and dispersant to obtain the spray material, and use a spraying machine to pump the spray material to the nozzle to spray the surface of the industrial kiln construction surface to obtain a spray protective layer.
[0088] The spraying pressure is 3MPa and the spraying speed is 15m 2 / s.
[0089] 2) Detection:
[0090] ① Before the spray protective layer is cured, the thermal shock stability of the spray protective layer is tested according to GB / T 30873; according to GBT41503-2022, amorphous refractory materials pneumatic nozzle mixing spray gun is used to prepare refractory spray material test blocks to test the rebound rate of the spray protective layer.
[0091] ③ After the sprayed protective layer is cured, the flexural strength of the sprayed protective layer is tested according to GBT 4513.6-2017 Unshaped refractory materials Part 6: Determination of physical properties; the compressive strength of the sprayed protective layer is tested according to GB / T 5072; the wear resistance of the sprayed protective layer is tested according to GB / T 18301, where the wear resistance is characterized by the wear amount (A) of the sample.
[0092]
[0093] According to Table 1 above and the instructions attached Figure 1 At least the following conclusions can be drawn:
[0094] ① The spray protective layer obtained by spraying the spray coating provided in the embodiment of the present application has the advantages of high strength, good wear resistance, flexural strength, compressive strength, strong thermal shock stability, low rebound rate, energy saving and environmental protection.
[0095] ② It can be seen from Examples 1 to 3 and Comparative Example 1 that the spray coating of the embodiment of the present application uses aluminum sol as a binder for silicon carbide material, which greatly improves the high-temperature performance of the material.
[0096] ③ It can be seen from Examples 1 to 3 and Comparative Examples 2 to 4 that in the spray coating of the embodiments of the present application, titanium dioxide, C in the asphalt and metal Si react in situ (reaction temperature 1350°C to 1450°C) to generate a Ti3SiC2 binding phase, and the reaction chemical formula is: 3TiO2+9C+2Si=Ti3SiC2+SiC+6CO. Ti3SiC2 has a high melting point (>3000°C) and good corrosion resistance. Its unique network structure and plastic properties at high temperatures can greatly reduce thermal stress and improve the thermal shock stability of the spray protective layer.
[0097] ③ By Figure 1 It can be seen that in the Ti3SiC2 binding phase, the structure of the network Ti3SiC2 phase wrapping the SiC particles can significantly improve the mechanical properties and high-temperature oxidation resistance of the wet spray coating, ultimately making the material have higher strength and wear resistance.
[0098] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. An aluminum sol combined with silicon carbide spray coating, characterized in that: The invention comprises the following components: base powder and external materials; The matrix powder includes silicon carbide, alumina, spherical asphalt, titanium dioxide and silicon; the additive includes aluminum sol, dispersant and accelerator; The mass fractions of the raw material components in the matrix powder include: 60% to 75% silicon carbide, 10% to 25% alumina powder, 2% to 7% spherical pitch, 1% to 5% titanium dioxide and 2% to 4% silicon; The dispersant is a mixture of polyethylene glycol polymer compound and sodium tripolyphosphate; The coagulant is a mixture of a saturated aluminum chloride solution and a saturated sodium chloride solution; The mass of the aluminum sol is 7% to 11% of the matrix powder; The mass of the dispersant is 0.1% to 0.35% of the matrix powder; The mass of the coagulant is 0.7% to 1.6% of the matrix powder.
2. The aluminum sol combined with silicon carbide spray coating according to claim 1, characterized in that: Taking the mass of the matrix powder as 100%, D represents the particle size of the silicon carbide, and the gradation distribution and mass fraction of the silicon carbide include: 5mm≤D<8mm is 10%~15%, 3mm≤D<5mm is 15%~25%, 1mm≤D<3mm is 15%~25%, 0.074mm≤D<1mm is 10%~20%, and D<0.074mm is 10%~20%.
3. The spray coating material according to claim 1, characterized in that: The D50 of the alumina powder is 1.0 μm to 2.0 μm.
4. The spray coating material according to claim 3, characterized in that: The particle size of the ball asphalt is less than 1 mm.
5. The spray coating material according to claim 4, characterized in that: The particle size of the titanium dioxide is less than 44 μm.
6. The spray coating material according to claim 5, characterized in that: The silicon has a particle size of 74 μm or less.
7. The spray coating material according to claim 1, characterized in that: In the aluminum sol, the mass fraction of Al2O3 is greater than 35%, the pH value is 3.5-4.5, and the average particle size is 10nm-100nm.
8. A spray protective layer, characterized in that: The raw material components in the spray coating protective layer include the spray coating material according to any one of claims 1 to 7, and the thickness of the spray coating protective layer is 50 mm to 100 mm.
9. A method for preparing a spray protective layer as claimed in claim 8, characterized in that: The steps include: Obtaining raw material components of the spray protective layer; The matrix powder, aluminum sol and dispersant are mixed, and then mixed with a coagulant and then sprayed on the surface of the target object to obtain the spray protective layer; The spraying pressure is 2MPa~4MPa, and the spraying speed is 10m 2 / s~20m 2 / s.
10. Use of the spray coating material according to any one of claims 1 to 7 in the field of industrial kilns.
Citation Information
Patent Citations
Preparation for producing refractory materials
CN101535211A
Al2O3-SiC-C castable used for blast furnace iron tapping channel and preparation method thereof
CN102391004A